(untitled) (Jurnal ForestrIndo, 2025)
Farmer participation in private forest management plays an important role in maintaining the existence of the forest and improving community welfare and forest sustainability. This study aims to analyze farmers’ participation in private forest management and its influencing factors in Kare Sub-district, Madiun District. Data were collected using in-depth interviews and ordinal scale questionnaires with Rank Spearman correlation analysis on 90 farmers by purposive sampling. Internal factors measured were age, number of family dependents, land size, farming experience, and farming motivation. External factors consisted of forestry extension, forest farmer groups, and information sources. The results showed that farmers’ participation in private forest management in Kare Sub-district at the planning stage was moderate, the implementation stage was moderate, the utilization stage was moderate, and the evaluation stage was low. Participation is significantly influenced by internal and external factors.